Appraisal of Salt Crystallisation and Rising Damp Problems in Building - Aw, Nien Wei; Othuman Mydin, Md Azree (Eftimie Murgu University of Resita, 2017)
It should be pointed out that salt crystallisation and rising dampness are two separate but interconnected processes. Both of these damages must be understood if damage is to be minimized and if corrective measures are to be successful. However, the term rising damp has been usually used to cover both aspects, it tends to overlook the role of salt, and issues that will increasingly significant due to the buildings are getting older and as the soils are becoming more saline. Hence this paper will focus on background and an understanding of salt crystallisation and rising damp problems. Furthermore, the discussion also will include the indications, causes and effects of both damages.